Change your brain, change your pain : breaking the doom loop to heal chronic physical and emotional pain - Amen, Daniel G. (Harper, an imprint of HarperCollinsPublishers, 2025)
"In the United States alone, one in five adults experiences chronic pain. For too long, when a doctor couldn't find the source of frequent pain, the patient was dismissively told, 'It's all in your head.' Today, we know that our somatic responses to trauma, anxiety, and depression create real suffering, and that physical pain can lead to trauma, anxiety, and depression. Dr. Daniel Amen calls this 'the doom loop'--the dance between physical and emotional pain. These doom loops interfere with our ability to live our lives. But we can shift the doom loop into a healing loop, and in this ... book, he shows us how"--